Palmprint recognition system based on gray level cooccurrence matrix - Caliskan, Abidin; Ergen, Burhan (IEEE Computer Society, 2014)
A biometric system provides automatic identification of individuals based on a unique feature or characteristic of the individuals. Palmprint biometric system has an important place among biometric identification systems because of its advantages. In this study, Gray Level Co-Occurence Matrix based palmprint recognition system which provides successful results for tissue type of image identifying has been proposed. Firstly, image coordinate system has been defined to facilitate image alignment for feature extraction. Then, region of interest is cropped from the palmprint images. The properties of the interested region have been determined using the developed system and it has been given to the classifier for recognition. © 2014 IEEE.
GRI seviye eş-oluşum matrisi tabanli avuç içi tanima sistemi
2014 22nd Signal Processing and Communications Applications Conference, SIU 2014 -- 23 April 2014 through 25 April 2014 -- Trabzon -- 106053
Keywords: Biometric system; Gray Level Co-occurrence Matrix; Palmprint recognition